Maladie hyperostosique et mode de vie : intérêt d’une démarche bio-archéologique. Exemple du cimetière du Couvent des Soeurs Grises de Beauvais (Oise), XVe-XVIIIe siècles - Sacha Kacki; Sébastien Villotte (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Within the framework of paleopathological studies, diffuse idiopathic skeletal hyperostosis (DISH) is sometimes associated with a particular way of life, especially with an overly rich diet. Medical data upon which this interpretation is based are discussed. The prevalence of DISH was evaluated in a sample of 305 adults from a convent cemetery. Eight proven cases and two probable cases of the disease were diagnosed. The influence of age could be checked and a strong male prevalence appeared. As the analysis of the historical texts indicates the existence of privileged places of burial, the space distribution of cases was studied. It indicates an important difference according to sectors, supporting a relationship between DISH and social status of the individuals. Our results support the assumption of an influence of the way of life on the expression of the disease which could be ascribable to feeding behaviours or individual longevity differences. This study confirms the usefulness of the joint application of historical, archaeological, and paleopathological data in the reconstitution of the way of life of past populations.